Burnout, resilience, and subjective well-being among Portuguese lecturers’ during the COVID-19 pandemic - Castro, Luísa; Serrão, Carla; Rodrigues, Ana Rita; Marina, Sílvia; dos Santos, José Paulo Marques; Amorim-Lopes, Teresa Sofia; Miguel, Carla; Teixeira, Andreia; Duarte, Ivone (Frontiers in Psychology, 2023)
Background: Lecturers face a large wide of occupational stressors. If the prolonged stress and the symptomatology associated with the working conditions to which lecturers were exposed were already a concern before the pandemic, the pandemic may have exacerbated this psychosocial vulnerability. Burnout is a psychological syndrome that develops in response to chronic work stress. This study aims to describe burnout among lecturers working in Portugal and to analyse potential determinants of burnout during the COVID-19 pandemic. Methods: A cross-sectional study was performed using an online questionnaire distributed via social networks. The survey collected sociodemographic and sleep patterns data in addition to applying the Copenhagen Burnout Inventory (personal, work-and student-related burnout), the Resilience Scale, the Depression Anxiety and Stress Scales, and the Satisfaction with Life Scale.2 This is a provisional file, not the final typeset article Results: The sample included 331 lecturers from 35 different colleges and faculties. Three significant models explained personal (R2=54%), work-(R2=47%) and student-(R2=19%) related burnout. Lower levels of resilience and higher levels of depression and stress were significantly associated with personal and work-related burnout. Changes in sleep patterns were additionally associated with both personal and work-related burnout. Conclusions: Higher education institutions must recognize the impact of the work environment and organizational culture on faculty mental health and take proactive measures to improve this environment. These institutions can implement support strategies such as educational technology training, professional development programs, emotional support resources, and workload flexibility. Implementing measures to enhance lecturers' resilience and overall life satisfaction could potentially help mitigate burnout and improve the well-being of educators, ultimately contributing to the overall quality of education.